Religioteinment Sebagai Fenomena Globalisasi: Sebuah Perspektif Antropologi Agama - Nayuf, Henderikus (Tumou Tou, 2021)
The focus of research in this paper is the impact of the online worship phenomenon when the government instructs all community activities, including worship, to be carried out from home. In principle, worship anywhere, open a problem for Christians. However, when the issue of worship is linked to the issue of consumerism and globalization, what appears is the relogical protein style. The principles of worship are calculated based on the terms digital marketplace and infoteinment. This is where the phenomenological approach can be used as a "scalpel" in seeing the value and meaning of consumerism and globalization from the perspective of religious anthropology. The result is that advances in communication technology must contribute to humanity. Humans must be placed as subjects in the use of communication technology to fulfill their spiritual needs.